Bioactive anti-aging agents and the identification of new anti-oxidant soybean peptides. (August 2021) - Amakye, William Kwame; Hou, Chuanli; Xie, Liping; Lin, Xiaoling; Gou, Na; Yuan, Erdong; Ren, Jiaoyan
Abstract: Degenerative diseases associated with aging could be attributed primarily to the deleterious effects of free radicals on cell constituents and connective tissues. The aim of this study was to compare the anti-aging effects of soybean (PHS), oyster (PHO), and sea cucumber (PHH) protein hydrolysates and then isolate and characterize the responsible anti-aging peptides of the most effective hydrolysate that could allow for the further development of anti-aging bioactive ingredients. Protein hydrolysates were prepared from the three natural products using Alcalase for the enzymatic hydrolysis. D-galactose-induced specific pathogen-free (SPF) Kunming mice were used to explore the anti-aging effects of the three hydrolysates. The results showed that the three protein hydrolysates all had a significant impact on reversing D-galactose-induced aging-associated learning and memory impairments and oxidative stress in the order PHS > PHO > PHH. Consistent with the activity in vivo, PHS also showed the strongest DPPH scavenging activity among the three hydrolysates. Consequently, PHS was further purified using DEAE-52 ion exchange resin into three fractions (Fa, Fb and Fc), of which Fa showed the highest antioxidative activity. Fa was subsequently purified using G-15 gel filtration chromatography. Using LC-MS/MS, two peptides, Trp-Pro-Lys (WPK) and Ala-Tyr-Leu-His (AYLH), were identified as the active components of the purified fraction. In vitro antioxidant analysis showed that the peptides strongly alleviated H2 O2 -induced oxidative damage in PC12 cells. The results suggested that PHS and its constituent peptides could be potentially effective antioxidant agents in functional foods or nutraceuticals for aging-related learning and memory impairments and oxidative stress. Graphical abstract: Image 1 Highlights: Soybean protein (PHS), oyster protein (PHO) and sea cucumber protein (PHH) hydrolysates were studied. In vivo anti-aging activity of the hydrolysates was in the order PHS > PHO > PHH. PHS showed the strongest DPPH scavenging activity. Peptides WPK and AYLH were purified from PHS using LC-MS/MS. Both peptides significantly inhibited H2 O2 -induced oxidative damage in PC12 cells.